What is retirement? A review and assessment of alternative concepts and measures - Frank T. Denton; Byron G. Spencer (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2008)
Since the concept of retirement is prominent in both popular thinking and academic studies it would be helpful if the notion were analytically sound, could be measured with precision, and would make possible comparisons of patterns of retirement over time and among different populations. This paper reviews and assesses the many concepts and measures that have been proposed, summarizing them in groupings that reflect nonparticipation or reduced participation in the labour force, receipt of pension income, endof-career employment, self-assessed retirement, or combinations of those characteristics. It concludes that there is no agreed measure and that no one measure dominates. Instead, new measures continue to be proposed to take account of additional refinements as new data sets become available, thereby further restricting possible comparisons. The confusing array of definitions reflects the practical problem that underlies the concept of retirement: it is an essentially negative notion, a notion of what people are not doing - namely, that they are not working. A more positive approach would be to focus instead on what people are doing, including especially their involvement in non-market activities that are socially productive, even if those activities do not contribute to national income as conventionally measured.
Keywords: J26; 330; concepts of retirement; measures of retirement